The Image of LANGUAGE in Lexicographical Sources. Analysis of Systematic Data - Smetonienė, Irena; Smetonienė, Anželika (Respectus Philologicus, 2018)
[full article, abstract in Lithuanian; only abstract in English] Language is one of the essential values of the nation, which encodes not only the culture and the identity of the nation, but also what is called national psychology. The article aims at revealing the image of the concept LANGUAGE in modern lexicographical sources. Attention is drawn to the fact that in the Dictionary of Lithuanian Language only 4 out of 10 meanings of ‘kalba’ (language) are witnessed in present-day spoken language, however, namely they show how the concept is understood by the users of the language. The Dictionary of Synonyms provides quite a few synonyms of the language but not all of them are equivalent. Synonyms ‘šneka’ (speech) and ‘žosmė’ are used in the same sense as the language. Another synonym ‘byla’ is quite close to the meanings of the language. However, it has more meanings and some of them are unrelated to the language. The study reveals that there are more contextual synonyms in the speech, such as ‘žodis’ (word), ‘liežuvis’ (tongue). The new meanings can also be highlighted by the antonyms but in the case of language, the Dictionary of Antonyms presents only one − ‘tyla’ (silence). There are more antonyms in the spoken language.